Feasibility of salvage decompressive surgery for pending paralysis due to metastatic spinal cord compression - Younsi, Alexander; Riemann, Lennart; Ishak, Basem; Scherer, Moritz; Unterberg, Andreas; Zweckberger, Klaus (Clinical neurology and neurosurgery, 2021)
Objective - Metastatic spinal cord compression (MSCC) is a frequent phenomenon in cancer disease, often leading to severe neurological deficits. Especially in patients with complete motor paralysis, regaining the ability to walk is an important treatment goal. Our study, therefore, aimed to assess the neurological outcome of patients with MSCC and complete motor paralysis after decompressive surgery. - Methods - Patients with MSCC and complete motor paralysis, surgically treated by decompressive surgery between 2004-2014 at a single institution were retrospectively analyzed. Clinical patient data were collected from medical records. To assess the neurological outcome, Frankel grade (FG) at admission and discharge were compared. Statistical analysis was performed to identify factors associated with an ambulatory status after surgery. - Results - Twenty-eight patients were included in this study. The majority of metastases (57 %) were located in the thoracic spine and 75 % showed extraspinal tumor spread. The median interval between loss of ambulation and surgery was 35 h (IQR: 29-70). Posterior circumferential decompression without stabilization was performed in all cases within 24 h of admission. Neurological function improved in 17 patients (63 %) and seven (26 %) even regained the ability to walk following surgery. The rate of complications was low (7%). In statistical analysis, only the Karnofsky Performance Index (KPI) displayed a significant predictive value for an ambulatory status at discharge. - Conclusions - Our findings indicate that severely affected MSCC patients with complete motor paralysis might benefit from decompressive surgery even when the loss of ambulation occurred more than 24 h ago.
Gesehen am 04.05.2021